Vocational Training in the US as an Anthropological Issue: International Exchange Programs for Scientists as a Framework for the Study of Distribution and Reproduction of Power - Saša Nedeljković (University of Belgrade, 2016)
The discourse of science is often used to validate or conceal the ways in which power is distributed and reproduced within a society. It is rarely, however, perceived or conceptualized in this manner. Certain aspects of professional scientific activity or the system of higher education are especially prone to use in such a manner: I am referring especially to international exchange programs for scientists and university professors. By participating in a program like this I was in the position to observe many aspects of this process which aren’t visible at first glance, and I was able to analyze them using the concept of power. In this paper I will attempt to give a detailed description and contextualization of the basic factors and actors of this process, and I will offer a model for future analyses of issues similar to this.